Association between fluoroquinolones and retinal detachment: insights from a large German health claims-based cohort study - Julia Wicherski; Jonas Peltner; Cornelia Becker; Katrin Schüssel; Gabriela Brückner; Andreas Schlotmann; Helmut Schröder; Winfried V. Kern; Britta Haenisch (BMC Ophthalmology)
Abstract Purpose Real-world evidence on fluoroquinolone-associated retinal detachment is contradictory. Therefore, we aim to examine the association between newly prescribed fluoroquinolones and the occurrence of retinal detachment with recent data from a large central European country. Methods A cohort study with an active comparator new user design was conducted. Dispensings of fluoroquinolone episodes were compared to a group of reference antibiotic episodes (amoxicillin, amoxicillin clavulanic acid, azithromycin, cefuroxime, cephalexin, clindamycin, sulfamethoxazole-trimethoprim, and doxycycline). Data from one of the largest statutory health insurances in Germany, the AOK, were used to follow up individuals with new antibiotic dispensing during the years 2014–2018 for the occurrence of retinal detachment. Piece-wise exponential additive mixed models adjusted for person-time, age, gender, comorbidities, year, and quarter at index were applied to estimate adjusted hazard ratios (aHR) with corresponding 95% confidence intervals (95% CI). Results In total, 15,232,585 antibiotic episodes were included in the cohort of which 0.05% episodes had an incident retinal detachment. The covariate-adjusted hazard ratio for fluoroquinolone episodes was 1.01 [0.95;1.08]. Likewise, in the propensity score-matched cohort the covariate-adjusted hazard ratio was 0.99 [0.92;1.07]. Moreover, there was little evidence for differences in age and gender subgroups, by follow-up time, selection of active comparator agent, dosage category, or censoring approach. Conclusions This large German cohort study found no meaningful real-world evidence for the association between fluoroquinolones and retinal detachment compared to a group of active comparator antibiotics.